Model Resolusi Konflik Berbasis Panca Kesadaran Santri dalam Tradisi Nahdlatul Ulama di Pondok Pesantren Nurul Jadid - Misbahul Arifin; Raudatul Jannah; Ahmad Fawaid (LAKPESDAM MWCNU Palengaan, 2026)
This study aims to analyze the conflict resolution model based on the Panca Kesadaran Santri (Five Consciousness of Santri) at Pondok Pesantren Nurul Jadid and its implications for strengthening religious moderation and student character. This study using a qualitative approach with a case study method. The results indicate that the internalization of Panca Kesadaran values encompassing religious, intellectual, social, organizational, and national consciousness serves as a cognitive foundation for navigating social dynamics within the pesantren environment. The operationalization of this model is achieved through strengthening human resource capacity, psychological counseling based on social-emotional learning, and the empowerment of